2023
DOI: 10.1186/s12888-023-04991-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental health stigma on loneliness, social isolation, and relationships in young people with depression symptoms

Katie Prizeman,
Netta Weinstein,
Ciara McCabe

Abstract: Background Major depressive disorder (MDD) is the most prevalent affective disorder and the leading cause of illness and disability among young people worldwide. Besides being more susceptible to the onset of depression, young people have a higher risk of loneliness, and their personal and social development is impacted by social relationships during this time. It is thought that mental health stigma can undermine both help-seeking and longer-term outcomes for disorders like depression in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 101 publications
2
3
0
Order By: Relevance
“…This may be due to a desire to avoid revealing vulnerabilities, causing concern, or disrupting the soothing nature of their interactions. Our findings align with previous studies that suggest individuals with depression may be hesitant to acknowledge their condition due to the guilt and stigma surrounding it ( 25 ). While keeping secrets can provide protection against stigma, it may ultimately result in negative consequences such as social isolation and loneliness ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may be due to a desire to avoid revealing vulnerabilities, causing concern, or disrupting the soothing nature of their interactions. Our findings align with previous studies that suggest individuals with depression may be hesitant to acknowledge their condition due to the guilt and stigma surrounding it ( 25 ). While keeping secrets can provide protection against stigma, it may ultimately result in negative consequences such as social isolation and loneliness ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…Social support from peers has been linked to adaptive functioning and is recommended as an intervention target to increase hope, reduce self-stigma, and combat loneliness (2,23). Previous studies have shown that stigma can increase loneliness by leading to avoidance of social situations (24,25).…”
Section: Reconstructing a Social Networkmentioning
confidence: 99%
“…When considering the role of stigma, our findings are consistent with the literature suggesting that higher levels of stigma may be associated with more severe depressive symptoms ( Musa et al, 2020 ; Prizeman et al, 2023 ). A critical aspect appears to be the significant moderating role that stigma plays between depression and resilience.…”
Section: Discussionsupporting
confidence: 90%
“…Severe disorders in social functioning are complications of depression disorders [ 54 ]. In a qualitative study by Prizeman et al, youths with depression described self-stigma as a factor that disrupts social relationships and provokes symptoms of depression, isolation and loneliness [ 55 ]. As a result, SSDS can be helpful in measuring social inadequacy.…”
Section: Discussionmentioning
confidence: 99%